Use of Silk Proteins to Form Organic, Flexible, Degradable Biosensors for Metabolite Monitoring - Xu, Meng; Jiang, Yanke; Pradhan, Sayantan; Yadavalli, Vamsi K. (Frontiers in Materials, 2019)
The development of sustainable and degradable biosensors and bioelectronics has implications for implantable systems, as well in addressing issues of electronic waste. Mechanically flexible and bioresorbable sensors can find applications at soft biological interfaces. While devices typically use metallic and synthetic components and interconnects that are non-degradable, or have the potential to cause adverse tissue reactions, the use of nature-derived materials and conducting polymers can provide distinct advantages. In particular, silk fibroin and sericin can provide a unique complement of properties, providing both structural and functional elements. Here, a fully organic, mechanically flexible biosensor in an integrated 3-electrode configuration is demonstrated. Silk sericin conducting ink is micropatterned on a silk fibroin substrate using a facile photolithographic process. Next, using a conducting polymer wire sheathed in silk fibroin, organic interconnects are used to form the electrical connections. This fully organic electrochemical system has competitive performance metrics for sensing in comparison to conventional systems, as verified by detection of a model analyte – ascorbic acid. The stability of the silk biosensor through biodegradation was observed, showing that the sensors can function for several days prior to failure. Such protein-based systems can provide a useful tool for biomonitoring of analytes in the body or environment for controlled periods of time, followed by complete degradation, as transient systems for various applications.